A new supramolecular heterosynthon [C–I⋯OC(carboxylate)] at work: engineering copper acetate cocrystals. Issue 40 (22nd September 2020) - Torubaev, Yury V.; Skabitsky, Ivan V.
Abstract : Carboxylate–iodine supramolecular heterosynthons in combination with energy frameworks can be reliably applied in engineering hybrid metal-carboxylate cocrystals. Abstract : A carboxylate⋯iodine supramolecular heterosynthon can be reliably applied in cocrystal engineering, using metal carboxylates as building blocks. Analysis of the energy framework of the exemplary paddlewheel crystal [Cu(OAc)2 MeOH]2 indicates a robust 1D chain and even 2D layer long-range synthon modules, which can be intactly transferred into cocrystals. However, this approach allows the identification of a "weak link" – i.e. layers where the C–H⋯OC hydrogen bonds between ([Cu(OAc)2 (MeOH)]2 ) n polymeric chains will be subject to substitution by I⋯OC halogen bonds during interaction with halogen bond donor co-formers. In contrast to the O–H⋯OC/C–H⋯OC catemeric crystals of pure acetic acid, the crystal design exercise based on the I⋯OC(carboxyl) supramolecular synthon afforded a 1 : 1 cocrystal of 1, 4-C6 F4 I2 and CH3 COOH, where the discrete centrosymmetric dimers of acetic acid are stabilized by I⋯OC(carboxyl) halogen bonds.